You almost convinced me i'm real and insert title here - Pastrana, Jose Narciso B. (College of Arts and Letters, University of the Philippines Diliman, 2017)
Metafiction, a genre of fiction that both creates and criticizes at the same time, is a genre that contains within it multiple different devices that manipulate the ontological status of literary works. This particular thesis focuses on the mise en abyme device, more specifically how the inner text of different works are manipulated. Two works by Jorge Luis Borges were used in this paper, namely, "Tlon, Uqbar, Orbis Tertius" and "Pierre Menard, Author of the Quixote". This thesis focuses on how the author manipulates the fictional author, the paratext of the inner texts and the actual written words of the inner texts. This thesis concluded that the main manipulation ongoing in these two works is that of the frame-break. The frame-break was found to be a technique that allows authors to discuss their works at the same time of their creation, to talk about it while speaking it into existence. This thesis then applied the frame-break to two works that not only features breaking frames but also using different forms to concretize the frame-break.